the stuatus of woman in school text bool the cose of kurdish language textbooks in kurdistan region - Abdullah, Bishkoj J. (Humanities Journal of University of Zakho, 2014)
This research aimed to know the position of the Kurdish women in the scholar books via analyzing the content of these books. The research sample consisted of the book of Kurdish language from the first till the sixth year of elementary school. In order to fulfill the aims the researcher reviewed many previous researches that dealt with the same matter and made an appropriate tool for the research، and the unit of analyses was the clear and hidden idea. The result showed that the Kurdish woman position in the research was more social and family because this sector had 67,5 % of repetition. At the end some recommendations and suggestions were made by the researcher.